Moving (Across) Borders: Performing Translation, Intervention, Participation - Brandstetter, Gabriele; Hartung, Holger (transcript, 2017)
As performative and political acts, translation, intervention, and participation are movements that take place across, along, and between borders. Such movements traverse geographic boundaries, affect social distinctions, and challenge conceptual categorizations – while shifting and transforming lines of separation themselves. This book brings together choreographers, movement practitioners, and theorists from various fields and disciplines to reflect upon such dynamics of difference. From their individual cultural backgrounds, they ask how these movements affect related fields such as corporeality, perception, (self-)representation, and expression.